1997
DOI: 10.5860/crl.58.6.550
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on the Outsourcing of Cataloging in Academic Libraries

Abstract: The authors conducted a survey on outsourcing of cataloging in academic libraries in order to determine the extent of outsourcing being done in academic libraries and the overall success of such projects. The survey instrument included questions about factors that might affect the decision to outsource, what reasons libraries had for outsourcing or not outsourcing, what was being outsourced, and how vendors were chosen. Libraries were also asked to evaluate the success of outsourcing projects. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In 1997, Libby and Caudle reported a smaller percentage of libraries participating in outsourcing. 73 The size of the collection and the number of current receipts were factors that affected the decision to outsource. Improved vendor quality, enhanced services, economic conditions, and priority changes may explain the wider acceptance of these services than in the past.…”
mentioning
confidence: 99%
“…In 1997, Libby and Caudle reported a smaller percentage of libraries participating in outsourcing. 73 The size of the collection and the number of current receipts were factors that affected the decision to outsource. Improved vendor quality, enhanced services, economic conditions, and priority changes may explain the wider acceptance of these services than in the past.…”
mentioning
confidence: 99%
“…Their argument against outsourcing also includes intangibles such as the quality of the service being provided and upholding the dignity of the profession, which should be factored into cost considerations and work decisions (Nuzzo, 1999). A survey on catalog outsourcing at academic libraries conducted in the late 1990s found that outsourcing was not a significant trend among academic libraries (Libby and Caudle, 1997). However, the study also found that larger academic libraries were more likely to outsource as the size and number of titles to catalog increased yearly.…”
Section: Outsourcing In Academic Librariesmentioning
confidence: 91%
“…While the purpose of this study was to match up libraries interested in cooperating, it again shows that, even with cataloging backlogs in languages which present some difficulty in handling, not all libraries are willing to outsource. Libby and Caudle (1997) mailed a survey to 187 academic libraries in 1997, finding that 33 respondents either were currently outsourcing cataloging, or had done so in the past. The authors' statistical analysis confirms that there is a significant correlation between size of library collection and the outsourcing of cataloging, but not between number of professional librarians and outsourcing.…”
Section: Surveys Regarding Specific Functionsmentioning
confidence: 99%